Barnes, John. Shed on the Barnes property 1. - Wang, Xuan (2013)
This shed is 14.5 x 13 feet and was built sometime before the 1940s, when the Barnes family acquired the property. Barnes and his father have both done renovations on the shed. It is presently painted red with white trim.